Polyhydroxyalkanoate production in Priestia megaterium strains from glycerol feedstock. - Andrew J Cal; Victor J Chan; Winston K Luo; Charles C Lee (PLoS ONE)
Our society relies heavily on plastic, but most plastic is petroleum-based and non-biodegradable resulting in major negative environmental impacts. Polyhydroxyalkanoates (PHAs) are a type of biopolymer that can be produced from microorganisms cultured on renewable feedstocks, such as glycerol. PHAs are biodegradable and have properties similar to petroleum-based plastics. Several Priestia megaterium isolates have been demonstrated in previous studies to produce PHA when cultured on glycerol, but there has been no comparison of strains available in public repositories. Such comparison would be useful to identify the most promising strains for further development. In this study, we screened a number of P. megaterium strains from readily accessible repositories for their ability to produce PHA from glycerol. The strains had a wide range of growth and PHA production characteristics on glycerol: cell dry weight (0.5-5.7 g/L), percent PHA (4-42%), PHA titer (0.1-1.9 g/L), and yield (26-303 mg/g). The time course of PHA production varied widely among the different strains. There was also a dramatic difference in molecular weights which ranged from 119 kD to 402 kD. This information will be valuable to groups in selecting a PHA strain to develop based on their specific requirements.